Characteristics of stratified coal reservoirs in Liupanshui coalfield of Guizhou Province and exploration and development direction of coalbed methane - QIU Wenci, SANG Shuxun, GUO Zhijun, HAN Sijie, ZHOU Xiaozhi, ZHOU Peiming, WU Zhangli, SANG Guoyun, ZHANG Binbin, GAO Wei (Youqicang pingjia yu kaifa)
Guizhou Province is rich in coalbed methane（CBM） resources; however, the development of tectonic coal constrains the increase of reserves and production. By studying the reservoir characteristics of tectonic coal in Guizhou, adaptable exploration and development technologies are proposed, providing a theoretical basis for the safe and efficient development of tectonic coal reservoirs in the province. Under the control of the heterogeneous mechanical properties of coal seams and the uneven distribution of tectonic stress fields, the phenomenon of stratification in tectonic coal is more prevalent. Taking the No. 11 coal seam in the Dahebian syncline of the Liupanshui Coalfield as an example, isothermal adsorption, mercury intrusion, low-temperature liquid nitrogen adsorption, and low-temperature CO2 adsorption experiments were conducted to study the physical properties of each stratified reservoir. The formation mechanism of tectonic coal stratification in thick coal seams and the CBM enrichment pattern were discussed. The adaptability and applicability of exploration and development technologies for CBM in thick coal seams with complex coal structures were compared. The results showed that:1） The average thickness of the No. 11 coal seam in the Dahebian syncline was 4.48 m, and the formation of thick coal seams was the result of a balance between basin subsidence rates and sedimentary supply. Under subsequent compressional and thrust tectonic activities, the No. 11 coal seam underwent compression, fracturing, and even interlayer sliding, leading to the development of stratification in tectonic coal. Stress was concentrated in the middle stratification, where the mechanical properties of the coal were weaker. 2） The No. 11 coal seam exhibited a “sandwich” structure in the vertical direction, consisting of primary structural coal on top, mylonitic coal in the middle, and fragmented coal at the bottom. 3） The middle coal reservoir had the highest proportion of micropores and the strongest adsorption capacity. The Langmuir volume of maximum adsorption followed the trend: middle stratification（16.55 cm³/g） > lower stratification（14.69 cm³/g） > upper stratification（13.96 cm³/g）. 4） The No. 11 coal seam in the study area formed a lithology-fault-hydraulic seal gas reservoir. Based on the stratified characteristics of the coal structure, three different development technology routes were compared, and the most applicable direction for CBM development was identified as constructing cavities in the soft stratification of tectonic coal using horizontal wells to achieve pressure relief and CBM extraction.